2014
DOI: 10.1088/1468-6996/15/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study of different physical treatments on cartilage matrix derived porous scaffolds for tissue engineering applications

Abstract: Native cartilage matrix derived (CMD) scaffolds from various animal and human sources have drawn attention in cartilage tissue engineering due to the demonstrable presence of bioactive components. Different chemical and physical treatments have been employed to enhance the micro-architecture of CMD scaffolds. In this study we have assessed the typical effects of physical cross-linking methods, namely ultraviolet (UV) light, dehydrothermal (DHT) treatment, and combinations of them on bovine articular CMD porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 38 publications
4
31
1
Order By: Relevance
“…2C), which has been observed previously [13, 14]. While previous studies have shown no change in porosity [24] or increasing pore size [35] with increasing CDM concentration, these discrepancies may be attributable to differences in the fabrication process of the CDM scaffolds. Studies that reported changes in porosity [24] and pore size [35] that conflicted with the findings of the current study fabricated CDM scaffolds via homogenization alone, which has been shown to result in larger CDM particle sizes of 322 μm [14].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…2C), which has been observed previously [13, 14]. While previous studies have shown no change in porosity [24] or increasing pore size [35] with increasing CDM concentration, these discrepancies may be attributable to differences in the fabrication process of the CDM scaffolds. Studies that reported changes in porosity [24] and pore size [35] that conflicted with the findings of the current study fabricated CDM scaffolds via homogenization alone, which has been shown to result in larger CDM particle sizes of 322 μm [14].…”
Section: Discussionsupporting
confidence: 64%
“…While previous studies have shown no change in porosity [24] or increasing pore size [35] with increasing CDM concentration, these discrepancies may be attributable to differences in the fabrication process of the CDM scaffolds. Studies that reported changes in porosity [24] and pore size [35] that conflicted with the findings of the current study fabricated CDM scaffolds via homogenization alone, which has been shown to result in larger CDM particle sizes of 322 μm [14]. In contrast, the current study synthesized CDM constructs from pulverized CDM power, which leads to fine particle sizes of 97 μm and has been shown to produce more consistent pore size and morphology compared to CDM scaffolds fabricated via homogenization alone [14].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Physical treatments were applied to the cartilage matrix derived (CMD) scaffolds to enhance the cross‐linking and hence to improve their mechanical properties. We showed that Ultra‐Violet irradiation (UV) and Ultra‐Violet+Dehydrothermal (UVDHT) treatments yield highly interconnected porous scaffolds with the best architecture and mechanical properties . The high porosity of the scaffolds, measured through our highly precise and accurate microvolumetric method provided easy cell penetration.…”
Section: Introductionmentioning
confidence: 99%